2020
DOI: 10.1177/0361198120954202
|View full text |Cite
|
Sign up to set email alerts
|

Object Detection-Based License Plate Localization and Recognition in Complex Environments

Abstract: Automatic license plate recognition (ALPR) has made great progress, yet is still challenged by various factors in the real world, such as blurred or occluded plates, skewed camera angles, bad weather, and so on. Therefore, we propose a method that uses a cascade of object detection algorithms to accurately and speedily recognize plates’ contents. In our method, YOLOv3-Tiny, an end-to-end object detection network, is used to locate license plate areas, and YOLOv3 to recognize license plate characters. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, in 2019, in the United States, Aliari and Sadabadi (13) applied the faster CNN (FCNN) method to analyze speed data over time and to identify congestion on highways. In 2020, in China, Tao et al (14) applied the YOLOv3 technique to recognize license plates and found that it recognized more than 99% of letters and numbers.…”
Section: Vehicle Passenger Detection Technologymentioning
confidence: 99%
“…Similarly, in 2019, in the United States, Aliari and Sadabadi (13) applied the faster CNN (FCNN) method to analyze speed data over time and to identify congestion on highways. In 2020, in China, Tao et al (14) applied the YOLOv3 technique to recognize license plates and found that it recognized more than 99% of letters and numbers.…”
Section: Vehicle Passenger Detection Technologymentioning
confidence: 99%
“…It is becoming increasingly common to use convolutional neural networks (CNN) in image recognition, such as image classification 1,2 and object detection. 3 Human pose estimation (HPE) 4 is a CNN-based computer vision technique, which uses a blend of regression and classification approaches to detect the composition of human bodies. It is possible, for instance, to adopt computer vision techniques based on HPE to help supervisors identify the behavior of humans.…”
Section: Introductionmentioning
confidence: 99%
“…In the current intelligent traffic field, accurate recognition of license plate information is not only conducive to the handling of traffic accidents, but also beneficial to traffic safety [1][2][3][4]. However, in the actual traffic situation, due to the installation position and established angle of the camera, the license plate in the camera image has a certain tilt angle in both horizontal and vertical directions [5][6][7]. This brings a lot of difficulties to license plate information recognition.…”
Section: Introductionmentioning
confidence: 99%